1999
DOI: 10.1152/ajpcell.1999.277.3.c531
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3-kinase is required for aldosterone-regulated sodium reabsorption

Abstract: Aldosterone, a steroid hormone, regulates renal Na+ reabsorption and, therefore, plays an important role in the maintenance of salt and water balance. In a model renal epithelial cell line (A6) we have found that phosphoinositide 3-kinase (PI 3-kinase) activity is required for aldosterone-stimulated Na+reabsorption. Inhibition of PI 3-kinase by the specific inhibitor LY-294002 markedly reduces both basal and aldosterone-stimulated Na+ transport. Further, one of the products of PI 3-kinase, phosphatidylinositol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
117
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 21 publications
8
117
0
1
Order By: Relevance
“…The effects of aldosterone and insulin or IGF-1 may be additive [17]. Insulin stimulates SGK1 and is thus expected to enhance ENaC activity and renal Na + reabsorption [6][7][8]. SGK1 contributes to the regulation of renal Na + excretion by aldosterone, insulin, and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of aldosterone and insulin or IGF-1 may be additive [17]. Insulin stimulates SGK1 and is thus expected to enhance ENaC activity and renal Na + reabsorption [6][7][8]. SGK1 contributes to the regulation of renal Na + excretion by aldosterone, insulin, and IGF-1.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 ENaC upregulation by mineralocorticoids requires activation through the PI3 kinase pathway, which mediates the stimulation of renal Na ϩ excretion by insulin and IGF1. 24 Thus, SGK1 may participate in the signaling of IGF1-induced alterations of renal Na ϩ transport and blood pressure. Acromegaly, which leads to enhanced release of IGF1, is a well-known cause of hypertension, and the IGF1 gene locus demonstrates linkage to blood pressure in twins.…”
Section: Discussionmentioning
confidence: 99%
“…However, its role has not attracted as much attention because, under normal conditions, basal PIP 3 levels are very low in cells, even though it is well known that PIP 3 can be generated from PIP 2 by activation of phosphotidylinositol-3-kinase (PI 3-K). Recent studies suggest that both aldosterone and insulin enhance Na ϩ transport by activating PI 3-K in A6 cells (26 -28) and that the concentration of PIP 3 in A6 cells is elevated in response to aldosterone (26). Recent studies have also shown that not only PIP 2 but also other anionic phospholipids, including PIP 3 , acutely regulate ENaC activity in A6 cells (18,29).…”
Section: Stimulation Of Steroid Receptors Increases Membrane Pip 3 Anmentioning
confidence: 99%